Change processes during intensive day programme treatment for adolescent anorexia nervosa: a dyadic interview analysis of adolescent and parent views - Colla, Amy; Baudinet, Julian; Cavenagh, Penny; Senra, Hugo; Goddard, Elizabeth (Frontiers in Psychology, 2023)
Background. Day programmes for severe adolescent anorexia nervosa (AN) offer an alternative to inpatient admission for some cases, but there is only one service of this kind in the UK. Processes of change during treatment for AN are currently poorly understood.This study aimed to explore how adolescents with AN and their parents understood the helpful and unhelpful factors and processes that impacted them during day hospital treatment for the adolescent's AN. Method. A critical realist paradigm was used to qualitatively explore the views of 16 participants. Participants were recruited from the Intensive Treatment Programme (ITP) at the Maudsley Centre for Child and Adolescent Eating Disorders (MCCAED) at the end of treatment. Dyadic Interviews Analysis (DIA) was used to compare and contrast the narratives of the seven adolescent-parent pairs after two inductive reflexive thematic analyses were conducted for the group of eight adolescents and the group of eight parents separately.Results. Eight subthemes across three themes were identified: 1) "Like me she didn't feel so alone anymore" -families connect with staff, peers, and each other; 2) "You have to eat because ITP say so" -the programme provides families with containment through its structure and authority; and 3) "I found that I was using the skills I learnt there like in multiple aspects of my life, not just around food" -Families take in new ideas and generalise these into their lives. These interconnected themes generated hope and change. However, helpful elements individually could be unhelpful if one or more of the other factors were missing. For example, staff firmness, which participants often found helpful (theme two), could be experienced as harshness when adolescents did not feel related to as individuals (theme one).Conclusions. The findings can be conceptualised within recent descriptions regarding therapeutic change, including epistemic trust and mentalisation. Treatment characteristics, such as intensity and containment, as well as illness-specific factors and processes, namely control and collaboration, the role of peer support, and the potential for family members to experience the impact of the adolescent's AN and treatment non-response as traumatic, are equally important to consider.